Pertumbuhan return sektor kesehatan dalam isu melandainya pandemi COVID-19 - Badoa, Blessiana Keziah; Kumenap, Chantika Jesica Tesalonika (Yayasan Widyantara Nawasena Raharja, 2023)
The positive stimulus for economic interests in the form of the lifting of restrictions on community activities (or PPKM) on 30 December 2022 by the Government of Indonesia tends to have an impact on investor preferences in investment decisions. The purpose of this study is to examine the growth and performance of stock returns in the case of the sloping of the COVID-19 pandemic which is followed by the repeal of PPKM. This study makes observations from 1 January 2023 to 30 April 2023 with listed firms in the healthcare sector as a sample. Specifically, this study finds that the average returns from shares on development boards and mainboards are still not optimal and have not experienced significant growth. In addition, this study also finds that the returns performance on risk of the two trading boards is not optimal.